Characterization of Oral Squamous Cell Carcinoma Associated Inflammation: A Pilot Study - Laliberté, Catherine; Ng, Nicole; Eymael, Denise; Higgins, Kevin; Ali, Aiman; Kiss, Alex; Bradley, Grace; Magalhaes, Marco A. O. (Frontiers in Oral Health, 2021)
Background: Oral squamous cell carcinoma (OSCC) is a devastating disease that is usually associated with a dense associated inflammatory infiltrate. Characterizing tumour-associated inflammation is critical to understand the pathogenies of tumour development and progression Methods: We have tested a protocol to analyze tissue and salivary immune cells and mediators of 37 patients with OSCC at different stages and compared to 8 chronic periodontitis patients and 24 healthy controls. Tissue analysis was based on fluorescent immunohistochemistry and inflammatory mediators were analyzed using a Luminex-based 30-Plex panel. Immune cells were analyzed using multichannel flow cytometry including CD45, CD66b, CD3, CD4, CD8, CD25, CD56, CD68, CD138, PD-1 and PD-L1. Results: We show an increase in OSCC-associated inflammation characterized by increased pro-inflammatory cytokines including IL-6, IL-8, TNF, and GMCSF and increased salivary immune cells. Conclusion: We described a new method to analyze salivary inflammatory markers that can be used in future studies to monitor disease progression and prognosis